LITERATURE STUDY ON THE EFFECTIVENESS OF THE BLENDED LEARNING MODEL IN DEVELOPING COUNTRIES - Rizki Fauzi; Suci Pole Mappaita; Zulvia Trinova (International Journal of Teaching and Learning, 2025)
This study examines the effectiveness of the blended learning model in developing countries through a literature review. Blended learning, which combines face-to-face and online learning, is believed to have the potential to improve the quality of education. Studies show that this model can increase learning motivation, provide a variety of learning resources, and enable more active interaction between students and teachers. However, the implementation of blended learning in developing countries faces significant obstacles, including problems with technological infrastructure, limited internet access, and technological readiness among both students and teachers. This study emphasises the need for multidisciplinary collaboration in terms of improving technological infrastructure, training in technological skills, and providing adequate educational resources so that the implementation of blended learning can be more effective. The results of this study are expected to provide insights for policy makers and educators in implementing and optimising the blended learning model in developing countries.